(untitled) (Strathmore Law Journal, 2022)
Article 165 (3) (d) of the Constitution of Kenya 2010 gives the High Court the power of constitutional interpretation and to uphold constitutional supremacy by declaring void any law that is inconsistent with the Constitution or invalid any act or omission contravening it. Within the current Kenyan context, judicial review of legislative action has become the common practice. The courts are constantly drawn into the realm of legislative matters at the national and devolved levels of government established under the Constitution. However, the High Court’s role is limited to interpretation only and it cannot compel Parliament to modify the legislative action contravening the Constitution. Conversely, where the Legislature disagrees with the Court’s assessment of what the constitutional norms require it cannot substitute the Court’s interpretation with its own. The courts are subsequently tasked with the delicate prospect of balancing the legal and political constraints that underlie any case of judicial review of legislative action. This paper develops a conceptual framework for assessing how courts, in general, go about exercising their power of judicial review of legislative action in a way that enables them to adhere to the requirements of the separation of powers doctrine, while considering the legal and political constraints under which they must operate. The resulting framework proposes four possible types of courts that may emerge based on how a court balances the legal and political constraints prevailing upon it.